Food Inflation and Political Stability: Understanding the Link in Nigeria - Gbadebo, Adedeji Daniel (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This study examines the complex relationship between food inflation and political stability in Nigeria, a country experiencing significant economic volatility and societal unrest. According to recent data from the National Bureau of Statistics (NBS), food costs are rising at an unprecedented rate, with inflation expected to exceed 40% by early 2024. Using the cost-push theory of inflation as a theoretical lens, the study investigates how insecurity, inadequate infrastructure, climate change, and currency depreciation have disturbed food production and supply systems. These disruptions have significantly reduced household purchasing power, leading to political discontent, civic unrest, and a decline in faith in government institutions. Using a survey approach, data were obtained from 285 respondents in Pategi LGA, Kwara State. ANOVA revealed a significant correlation between food inflation and political instability (p < 0.05). The findings highlight how continuous increases in food prices fuel political discontent, particularly among economically disadvantaged communities. Furthermore, popular cynicism about the success of present government initiatives, such as the Anchor Borrowers Program, underlines the insufficiency of policy solutions. The study suggests that food inflation is more than just an economic concern; it is a powerful political force with the potential to erode democratic governance. The recommendations include proactive, security-driven agriculture policy, infrastructure development, market system reform, and transparent governance practices.